Usefulness and the Risks of Fintech payment for SMEs in Ambon City - Micrets Agustina Silaya (MediaTrend, 2022)
The development of information technology makes people today tend to want to carry out their activities practically and quickly. The financial sector is one of the most affected by technological developments. The manifestation of the development of technology and information in the financial sector is the emergence of financial technology (fintech). Fintech can help Micro, Small and Medium Enterprises (SMEs) during the current pandemic as a form of business innovation that is expected to increase market share, as well as a step in overcoming problems related to capital financing, preparation of financial reports, payments and marketing, and financial transactions. and other financial literacy. The use of a technology certainly always provides benefits to its users, but there is always a negative side, namely the risks that will accompany it.This study aims to determine and analyze the influence of the Usefulness and Risk of Fintech SMEs in Ambon City. This study uses a quantitative method by distributing surveys to 54 SMEs in Ambon City using convenience sampling technique.The test results with SEM-PLS show that perceived trust, perceived risk and perceived usefulness affect the intention to use fintech payments for SMEs actors. Trust is the strongest factor in encouraging the intention to use fintech payments. For perceived ease of use and perceived risk have no effect on attitude and perceived usefulness. attitude has no effect on the intention to use fintech payment. Based on the path value calculation, the most powerful factor influencing the intention to use fintech payments is perceived trust.